Pemikiran Pendidikan Islam Mohammad Natsir - Jeffri Hasibuan; Salman Paris Nasution; Muhammad Syaifuddin (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
Islamic education delves into the profound aspects of the individual, where knowledge is regarded as a divine gift that must be utilized in fulfilling the human role as a khalifah (steward) on Earth. The main challenge facing Islamic education today is the dichotomy between religious and secular knowledge. This study explores the thoughts of Mohammad Natsir, an Indonesian Muslim intellectual, who sought to formulate an Islamic education system that aligns with the demands of religion, nation, and state. Using a qualitative descriptive approach and library research, this study concludes that: 1) Natsir’s thoughts on Islamic education are based on the Qur'an and Sunnah, emphasizing the importance of an integral, harmonious, and universal education to develop human potential as khalifah. 2) Natsir’s relevance in the reform of Islamic education includes a purification process returning to pure Islamic teachings with tawhid (monotheism) as the foundation of education, and modernization through the integration of religious and secular education to overcome the dichotomy in Indonesia’s educational system.